2022
DOI: 10.53730/ijhs.v6ns1.6112
|View full text |Cite
|
Sign up to set email alerts
|

To compare the levels of salivary Interleukin 6 between oral potentially malignant disorders and oral squamous cell carcinoma

Abstract: To compare the levels of salivary Interleukin 6 between oral potentially malignant disorders and oral squamous cell carcinoma. After ethical clearance and informed consent, the saliva samples were collected from 20 patients of OPMD’S, 20 patients of OSCC and 10 controls. Salivary IL-6 levels were detected by enzyme linked Immunosorbent essay and appropriate statistical analysis was done. Significant differences in IL-6 concentration between OSCC, OPMD’S and controls were noted. Salivary IL-6 levels were higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Analogous with our study, a recent study done by Harshy et al . in 2022,[ 22 ] in comparing the levels of salivary IL-6 between 20 cases of OPMDs and OSCCs suggested that salivary IL-6 was statistically significant. In our study, there was statistical significance when comparing the salivary IL-6 between OSCC, OPMDs and CP and healthy controls which was not in accordance with the study done by St John et al .,[ 23 ] that indicated that IL-8 in saliva and IL-6 in serum hold the most promise as biomarkers for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous with our study, a recent study done by Harshy et al . in 2022,[ 22 ] in comparing the levels of salivary IL-6 between 20 cases of OPMDs and OSCCs suggested that salivary IL-6 was statistically significant. In our study, there was statistical significance when comparing the salivary IL-6 between OSCC, OPMDs and CP and healthy controls which was not in accordance with the study done by St John et al .,[ 23 ] that indicated that IL-8 in saliva and IL-6 in serum hold the most promise as biomarkers for OSCC.…”
Section: Discussionmentioning
confidence: 99%